1996
DOI: 10.1007/s001320050054
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Veränderungen der Halswirbelsäule

Abstract: Standard radiography of the cervical spine is still the first imaging procedure applied in degenerative disease of the cervical spine. Spondylosis deformans, osteochondrosis and uncovertebral arthrosis are well depicted by such images. Whether or not additional imaging is needed depends on the clinical symptoms. Special projections (anteroposterior oblique radiographs, lateral radiographs in flexion and extension) may be the next step. For many abnormalities, mainly of the intervertebral discs and the myelon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…Post-Myelo-Cf erlaubt zum einen die exakte geome trische Vermessung des Spinalka nals und zum ande re n eine exakte Etagenlok alisatio n de r pa tho morphologisehe n Befunde [9, 22,28]. D ie Vermessung de s Spinalkan als kan n in der Cf bezüglich a.p-D urchmesser und int raspinaler R äche sehr genau erfolgen.…”
Section: Diagnostik Der Spinalstenoseunclassified
See 1 more Smart Citation
“…Post-Myelo-Cf erlaubt zum einen die exakte geome trische Vermessung des Spinalka nals und zum ande re n eine exakte Etagenlok alisatio n de r pa tho morphologisehe n Befunde [9, 22,28]. D ie Vermessung de s Spinalkan als kan n in der Cf bezüglich a.p-D urchmesser und int raspinaler R äche sehr genau erfolgen.…”
Section: Diagnostik Der Spinalstenoseunclassified
“…Lumbal spricht ma n nac h Verbiest bei einem a.p.-Durchmesser < 10 mrn vo n einer abso luten und vo n 10-12 mm von eine r relativen Stenose [55]. Zervikal liegt ein e nger Spinalka nal bei ei ne m Spinalkanaldurchmes ser < 14 mm vor [28,40]. D a die Fo rm des Spina lkana ls inte run d intraindividu ell stark variert , ist die A ussagekraft de s a.p.-D urc hmessers begrenzt, z, B. bei der Kleebl attform.…”
Section: Diagnostik Der Spinalstenoseunclassified
“…Recent studies have shown that reconstruction in chronic rupture forms in which muscle atrophy has already occurred did not always appear appropriate. However, an earliest possible reconstruction must be aimed for in young patients, because of high functional demands [8]. Various reconstructive procedures have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Drei Tiere mussten aufgrund neurologischer Defizite vorzeitig getötet werden. Da der Belastungsapparat insgesamt nur 80 g wiegt, stellte er für die Kaninchen kaum eine zusätzliche Belastung da.Die Höhenminderung der Bandscheibe, Osteophythenbildung und subchondrale Sklerosierungen der angrenzenden Wirbelkörper sind typische Phänomene der menschlichen Bandscheibendegeneration[2,19,20]. Bandscheibengewebe besteht aus einem elastischen Material und kann sich so unter mechanischer Belastung verformen[21].…”
unclassified